PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA D’BRO CHICKEN & BURGER CIAWI - Safanah Zulfah; Safira Seftiyani; Lulu Adla Aulia; Halawatin Nisa; Apri Setiawan AR; Insan Saputra (MANAJEMEN, 2025)
This study analyzes the effect of service quality and product quality on purchasing decisions at D'Bro Chicken & Burger Ciawi given the importance of these two factors in the competitive culinary industry. Using quantitative methods, data were collected through Likert questionnaires from 50 respondents with purposive sampling and analyzed using multiple linear regression. The results show that service quality and product quality have a significant positive effect on purchasing decisions with a contribution of 0.343 and 0.337 respectively. The R² value of 71.8% shows that the two variables are able to explain the majority of variations in consumer purchasing decisions.